Near-complete reference genome assembly of Hoya carnosa - Yanfeng Kuang; Kunyue Ouyang; Meng Xia; Chao Feng; Ming Kang (Scientific Data)
Abstract Hoya R. Br. is the largest genus in the tribe Marsdenieae (Apocynaceae), comprising 350–450 species. Hoya species are popular in horticulture for their distinctive floral traits and fragrances, primarily sourced from domestication and mutation breeding. However, the lack of molecular analysis for floral morphological traits has limited their cultivation and application. In this study, we assembled a near-complete reference genome for H. carnosa, the model species of the genus, using PacBio HiFi reads and Hi-C method. The genome size was approximately 465.7 Mb with a contig N50 of 39.3 Mb. 99.7% of the sequences were anchored to 11 pseudochromosomes, and the assembly achieved a BUSCO score of 98.5%. We predicted 24,309 protein-coding genes, of which 90.2% (21,927) were functionally annotated. This high-quality genome provides a valuable reference for the research of evolution, conservation and molecular breeding in Hoya.